The Role of Citizen Journalism in Documenting and Reporting Climate Change and Adaptation Efforts - Mwendwa, Mildred; Mutethia, Paul Mutethia Diki (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Citizen journalism has emerged as a pivotal force in documenting and reporting climate change and adaptation efforts. This phenomenon leverages the accessibility and immediacy of digital platforms, enabling ordinary individuals to contribute valuable data and narratives that complement traditional media and scientific discourse. This paper explores the multifaceted roles of citizen journalists in climate change documentation, highlighting its contributions to raising awareness, providing real-time data, and influencing policy through grassroots engagement and fostering community resilience. By leveraging social media platforms and digital tools, citizens can document environmental changes, and share local adaptation strategies. This paper examines case studies, highlighting the effectiveness and challenges of citizen journalism in climate reporting. It concludes with recommendations for enhancing the credibility and impact of citizen-driven climate narratives. The study is grounded in the theories of participatory communication and public sphere. Participatory communication theory posits that inclusive and active involvement of community members in communication processes leads to more democratic and effective outcomes. This aligns with the role of citizen journalism, where community members actively document and report on climate change. Public sphere provides a framework for understanding how citizen journalism creates a platform for public discourse, enabling the exchange of ideas and fostering democratic engagement in climate change discussions. The study will adopt a descriptive survey design using both quantitative and qualitative approaches. Data will be collected using Focus Group Discussions, Key Informant Interviews, Questionnaires, Observations, Secondary Data, and Digital Data Analysis. Data will be analyzed using both descriptive and inferential statistics. The study acknowledges numerous potential limitations such as generalizability since findings may not be generalizable across different contexts due to cultural, social, and environmental differences, transferability of findings may be limited by lack of infrastructure, internet accessibility and community engagement levels. The findings will be disseminated through learned conferences, seminars, and workshops.